Plasma levels of adipokines in systemic lupus erythematosus patients. (October 2016) - Zhang, Tian-Ping; Li, Hong-Miao; Leng, Rui-Xue; Li, Xiang-Pei; Li, Xiao-Mei; Pan, Hai-Feng; Ye, Dong-Qing
Highlights: Plasma levels of the six adpokines do not differ between SLE and normal controls. Omentin-1 level is lower in SLE patients without nephritis. Chemerin and cathepsin-S level are higher in SLE with nervous system disorder. Abstract: Objective: To evaluate the plasma levels of six adipokines, including chemerin, omentin-1, lipocalin-2, cathepsin-S, cathepsin-L and adipsin, in patients with SLE. Methods: Ninety SLE patients and ninety control subjects were recruited, plasma adipokines levels were measured by enzyme-linked immunosorbent assay, and their associations with major clinical and laboratory indexes were analyzed. Results: There were no significant differences in plasma chemerin, omentin-1, lipocalin-2, cathepsin-S, cathepsin-L and adipsin levels between SLE patients and controls. Further subgroup analyses by major clinical and laboratory indexes showed that plasma omentin-1 level was significantly lower in SLE patients without nephritis when compared with those patients with nephritis ( P  = 0.002). Plasma chemerin, cathepsin-S levels in SLE patients without nervous system disorder were significantly lower in comparison with SLE patients with nervous system disorder ( P  = 0.035, P  = 0.029). No significant associations of other adipokines with any major clinical and laboratory indexes were observed. Conclusions: Plasma levels of chemerin, omentin-1, lipocalin-2, cathepsin-S, cathepsin-L and adipsin in SLE patients were not markedly different from the normal controls. The presence of nephritis was connected with higher plasma omentin-1 levels in SLE patients, and the presence of nervous system disorder was associated with higher plasma chemerin, cathepsin-S levels in SLE patients. However, functional studies are awaited to further explore the potential roles of these cytokines in SLE.